Resposta :
Resposta:
[tex]a_{4} = 9[/tex]
[tex]s_{5}=35[/tex]
Explicação passo a passo:
Observe o termo geral da PA
[tex]a_{n}=a_{1} + (n-1)*r[/tex]
Então,
[tex]a_{2} = a_{1} + r \rightarrow a_{1} = a_{2} - r[/tex]a_{2} = a_{1} + r \rightarrow a_{1} = a_{2} - r
Substituindo na primeira equação:
a_{n} = a_{2} - r + n*r - r = a_{2} + n*r -2r
Se n=7 então
[tex]a_{7} = a_{2} + 7r - 2r\\15 = 5 +5r\\5r = 15 - 5\\r= 10/5 \\r=2[/tex]
Logo,
[tex]a_{1} = a_{2}-r=5-2=3[/tex]
[tex]a_{4}=a_{1} + (n-1)\cdot r = 3 + 3\cdot 2 = 9[/tex]
Observe:
[tex]a_{5}=a_{1}+(n-1)\cdot r = 3+(5-1)\cdot 2 = 11[/tex]
Pela fórmula da soma da PA:
[tex]s_{n}=\frac{(a_{1}+a_{n})\cdot n}{2} \\\\[/tex]
[tex]s_{5} =\frac{(3+11)\cdot 5}{2} = \frac{70}{2}\\\\s_{5}=35[/tex]